Conducting Tests on the Competencies of A Future Teacher Teaching A Foreign Language (Eurasian Journal of Learning and Academic Teaching, 2023)
The article examines the system of international assessment of Arabic language proficiency, important personal and social characteristics of the pedagogical competence of a future Arabic teacher in achieving professional success, strategies that a future teacher should follow when teaching Arabic to people who do not speak аrabic.